Evaluation of the safety and quality of Brazil nuts (Bertholletia excelsa) using the tools of dna sequencing technology and aflatoxin profile - Esperança, Victor J. R.; Moreira, Paula I. O.; Chávez, Davy W. H.; Freitas-Silva, Otniel (Frontiers in Nutrition, 2024)
Introduction Brazil nuts (BNs) result from sustainable extraction and are widely exploited in the Amazon region. Due to the production characteristics in the forest and the nutritional characteristics of these nuts, the occurrence of fungal contamination and the presence of aflatoxins are extensively discussed in the literature as a great aspect of interest and concern. This study aims to evaluate the microbial profile through DNA sequencing and amplification of 16S and ITS genes for bacterial and fungal analysis, respectively, and the presence of mycotoxins using high-performance liquid chromatography with fluorescence detection (HPLC-FD) from different fractions of the nuts processed. Methods The BN samples, harvest A (HA) and harvest B (HB), from two different harvests were collected in an extractive cooperative in the Amazon region for microbiological analysis (from DNA extraction and amplification of 16S genes, bacteria analysis, and ITS for fungi) and mycotoxins (aflatoxins AFB1, AFB2, AFG1, and AFG2) using HPLC-FD/KobraCell®. Results and discussion The samples showed a very different microbiome and aflatoxin profile. Genera such as Rothia (HA) and Cronobacter (HB) were abundant during the analysis of bacteria; as for fungi, the genera Aspergillus, Fusarium, Penicillium, and Alternaria were also considered prevalent in these samples. Soil microorganisms, including those pathogenic and related to inadequate hygienic-sanitary production practices, as well as aflatoxins, were found in the samples. However, they were within the established limits permitted by Brazilian legislation. Nuts have a diverse microbiota and are not restricted to fungi of the genus Aspergillus. The microbiological and toxicological profile can vary significantly within the same nut in the same extraction region and can be exacerbated by global climate changes. Therefore, it is necessary to advance sanitary educational actions by applying good production practices and inspection programs to ensure the sustainability and quality of the BN production chain.